Communist anniversaries as a symphony of power and science (case study of Bulgaria) - Ewelina Drzewiecka (Studia Historiae Scientiarum)
The aim of the paper is to show the interplay between the power and the science in the context of cultural memory. The focus is on the Cyrillo-Methodian anniversaries in Bulgaria in the communist period, and the object of the analysis is the anniversary of 1969. The context relates to the process of development of new historiography and the functionalization of the nation-centric narrative. The main issue discussed is how the Communist Party, as a political institution, and the Bulgarian Academy of Science, as an academic institution, cooperated to establish a new vision of society. The discussion offers an interpretation in the light of the Orthodox concept of the symphony of power perceived as a metaphor of the relation between the secular and the spiritual power.